Use of urban green spaces: a case study in Taman Merdeka, Johor Bahru - Nor Akmar Abdul Aziz; Mohamed Daniel Mohamed Mokhtar; Thivya Laxshmy Raman; Fiffy Hanisdah Saikim; Nordiana Mohd Nordin (Universiti Putra Malaysia, 2020)
This study attempts to identify the use patterns and factors influencing the use of urban green space in Taman Merdeka, Johor Bahru. The aim of this investigation is to provide more crucial information to the field of urban green space study, especially in Malaysia. For this purpose, a total of 356 questionnaires were distributed to park users of Taman Merdeka. The questionnaire consists of several multiple-choice questions, open-ended questions, and questions that respondents answered based on the Likert scale. Data collection was done through convenience sampling. Results showed that most users of the park are Malays, consisting of an even percentage of male (49.4%) and female (50.6%) users, and are largely young adults in the age range of 26-32 years. This study also revealed that those living within 2 km radius from the park visit this recreation area more frequently compared to those living more than 10 km away from the place. Most users agreed that they visit Taman Merdeka for restorative health purposes and escaping from the stressful activities of the busy city lifestyle. The findings of this study are useful for future planning and management of urban green space in Malaysian cities.